A database for distributed manufacturing control - Skinner, Alan; Hutchison, David; Armitage, Bruce (Zielona Góra: Uniwersytet Zielonogórski)
This paper describes a database used for the control of a small manufacturing cell. The data used to control the manufacturing operation is distributed around the cell. Control is achieved by producing a piece of data (eg. the detection of a workpiece) at one node and duplicating that data on a second node. Access to the data is made via a Local Area Network (LAN).
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka